Anti-press violence in subnational undemocratic regimes: Veracruz, Gujarat, and beyond - Bartman, Jos (The Palgrave Macmillan series in international political communication, 2023)
Chapter 1: Introduction -- Chapter 2: Theoretical Framework -- Chapter 3: Research Design and Methodology -- Chapter 4: The Targeting of Journalists in Mexico -- Chapter 5: The Repression of Journalists in Veracruz -- Chapter 6: Boundary-blurring actors in Gujarat -- Chapter 7: Conclusions.